Investigating Nonalcoholic Fatty Liver Disease in a Liver-on-a-Chip Microfluidic Device - Gori, Manuele; Simonelli, Maria Chiara; Giannitelli, Sara Maria; Businaro, Luca; Trombetta, Marcella; Rainer, Alberto (PLOS ONE, 2016)
Background and Aim Nonalcoholic fatty liver disease (NAFLD) is a chronic liver disease worldwide, ranging from simple steatosis to nonalcoholic steatohepatitis, which may progress to cirrhosis, eventually leading to hepatocellular carcinoma (HCC). HCC ranks as the third highest cause of cancer-related death globally, requiring an early diagnosis of NAFLD as a potential risk factor. However, the molecular mechanisms underlying NAFLD are still under investigation. So far, many in vitro studies on NAFLD have been hampered by the limitations of 2D culture systems, in which cells rapidly lose tissue-specific functions. The present liver-on-a-chip approach aims at filling the gap between conventional in vitro models, often scarcely predictive of in vivo conditions, and animal models, potentially biased by their xenogeneic nature. Methods HepG2 cells were cultured into a microfluidically perfused device under free fatty acid (FFA) supplementation, namely palmitic and oleic acid, for 24h and 48h. The device mimicked the endothelial-parenchymal interface of a liver sinusoid, allowing the diffusion of nutrients and removal of waste products similar to the hepatic microvasculature. Assessment of intracellular lipid accumulation, cell viability/cytotoxicity and oxidative stress due to the FFA overload, was performed by high-content analysis methodologies using fluorescence-based functional probes. Results The chip enables gradual and lower intracellular lipid accumulation, higher hepatic cell viability and minimal oxidative stress in microfluidic dynamic vs. 2D static cultures, thus mimicking the chronic condition of steatosis observed in vivo more closely. Conclusions Overall, the liver-on-a-chip system provides a suitable culture microenvironment, representing a more reliable model compared to 2D cultures for investigating NAFLD pathogenesis. Hence, our system is amongst the first in vitro models of human NAFLD developed within a microfluidic device in a sinusoid-like fashion, endowing a more permissive tissue-like microenvironment for long-term culture of hepatic cells than conventional 2D static cultures.